2022
DOI: 10.3389/fpsyt.2022.853464
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory Analysis of Suicidal Ideation in Spanish College Students Using Ecological Momentary Assessment

Abstract: IntroductionSuicide is a preventable death in young people. It is well known that suicide behavior is a multicausal phenomenon. However, suicidal ideation (SI) commonly underlies suicide, and Ecological Momentary Assessment (EMA) can help us to better characterize it and its risk and protective factors in the short term. We aimed, first, to investigate the estimated prevalence and trajectories of SI in a community sample of Spanish college students using an EMA methodology and, second, explore the associations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 86 publications
(99 reference statements)
1
1
0
Order By: Relevance
“…In contrast, in the present study, positive affect was negatively associated with all three dimensions of suicidal ideation (pessimism, sleep, and despair). These results are consistent with previous findings that positive affect is a protective factor against suicidal ideation (Brent et al, 2013 ; Cha et al, 2018 ; Horwitz et al, 2021 ; Layron Folgado et al, 2022 ; Schatten et al, 2021 ). Furthermore, lower positive affect is prospectively related to suicidal ideation and individuals with suicidal ideation report significant lower positive affect than those without suicidal ideation (Bennardi et al, 2019 ; Tian et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, in the present study, positive affect was negatively associated with all three dimensions of suicidal ideation (pessimism, sleep, and despair). These results are consistent with previous findings that positive affect is a protective factor against suicidal ideation (Brent et al, 2013 ; Cha et al, 2018 ; Horwitz et al, 2021 ; Layron Folgado et al, 2022 ; Schatten et al, 2021 ). Furthermore, lower positive affect is prospectively related to suicidal ideation and individuals with suicidal ideation report significant lower positive affect than those without suicidal ideation (Bennardi et al, 2019 ; Tian et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…Recently, Layrón‐Folgado et al. (2022) found that higher levels of meaning in life were representative of university students with low levels of suicide ideation.…”
Section: Introductionmentioning
confidence: 99%